A RECORD OF GASTROPODS AND BIVALVES COLLECTED FROM EAST ANTARCTICA BY THE JAPANESE ANTARCTIC RESEARCH EXPEDITIONS IN 1992-94 (17th Symposium on Polar Biology) - ヌマナミ, ヒデキ; オクタニ, タカシ; イワミ, テツオ; タケウチ, イチロウ; イガラシ, アツオ; ツチヤ, ヤスタカ; フクチ, ミツオ; NUMANAMI, Hideki; OKUTANI, Takashi; IWAMI, Tetsuo; TAKEUCHI, Ichiro; IGARASHI, Atsuo; et al. (National Institute of Polar Research, 1996)
P(論文) Benthic Mollusca were collected with baited traps and by SCUBA diving near Syowa Station, and with the beam-trawl at nine stations in the areas of Lutzow-Holm Bay, Casey Bay and Prydz Bay, East Antarctica. Around Syowa Station, 7 gastropods and 3 bivalves were collected. Large size specimens collected with the beam-trawl include 8 gastropods and 3 bivalves from Liitzow-Holm Bay, 7 gastropods from Casey Bay and 2 gastropods and 4 bivalves from Prydz Bay. Almost all species have circum-Antarctic distribution. Among them Aforia multispirallis (Turridae), which had hitherto been reported from the South Orkney Islands, the South Shetland Islands and the Antarctic Peninsula, was collected from Prydz Bay for the first time. This indicates that the distribution of the species is extended further eastward than previous records. The species composition of the present collections represents a typical shelf fauna in Antarctica. departmental bulletin paper